Effects of rocky desertification on soil bacterial community in alpine grasslands of the Qinghai-Tibet Plateau - Li, Shan; Zhou, Huakun; Wang, Wenying; Ade, Haze; Zhang, Zhonghua; Ma, Li; Wang, Zhen; Zhang, Qiang; Wei, Jingjing; Su, Hongye; Qin, Ruimin; Shi, Zhengchen; et al. (Frontiers in Microbiology, 2025)
The makeup of soil microbial communities may serve as a crucial predictor of the alpine grassland ecosystem. Climate change and human disturbance have resulted in intensified ecosystem degradation, such as grassland rocky desertification, which may modify the structures and composition of the microorganisms. However, little is known about the effects of rocky desertification on soil microbial communities of soil. Here, we investigated five different layers of rocky desertification grassland in the Qinghai-Tibet Plateau, including nil rock desertification (NRD); potential rocky desertification (PRD); light rocky desertification (LRD); moderate rocky desertification (MRD); and severe rocky desertification (SRD), we compared soil bacterial community with soil physiochemical properties in different rocky desertification conditions. The result showed that rocky desertification significantly altered the physiochemical properties of the soil but did not significantly affect the bacterial community microbial abundance and diversity. At the same time as rocky desertification increased, soil organic carbon (SOC), total nitrogen (TN), alkali hydrolyzable nitrogen (AN), available phosphorus (AP), and available potassium (AK) decreased significantly, while soil pH, total phosphorus (TP); and total potassium (TK) increased. Redundancy analysis revealed that pH, AK, TP, and SOC are key factors influencing soil bacterial communities. Our finding provides basic information and scientific reference for the restoration of the rocky desertification of alpine grasslands.